Dyslipidaemia Among Bangladeshi Children and Adolescents with Type-1 Diabetes: An Observational Study (Bangladesh Journal of Child Health, 2022)
Introduction: Dyslipidemia increases the frequency and severity of micro and macrovascular complications of type 1 diabetes (T1D).Materials & Methods: This cross-sectional study was aimed to evaluate the frequency of dyslipidaemia and its association with other risk factors in children and adolescents with type 1 diabetes. A total of 397 Type 1 diabetes (T1DM) patients aged 10-18 years who attended, Paediatric diabetes clinic in BIRDEM over one year period were included in this study.Results: The overall frequency of dyslipidaemia was 63.5% and median duration of diabetes was 3.0[2.0- 5.0 years]. The High LDL was most cmmmon dyslipidaemia (81%) in our study population. FBS was significantly higher 12.8[10.0-15.5] vs 10.8[7.7- 12.6] (p